2011
DOI: 10.1016/j.anpedi.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad de Ollier: tumores benignos con riesgo de malignización. Revisión de 17 casos

Abstract: ResumenObjetivo: Analizar una larga serie de esta rara entidad para entenderla mejor y valorar el riesgo de malignización y comprender esta enfermedad infrecuente para el correcto diagnóstico y tratamiento. Material y métodos: Diecisiete casos de encondromatosis múltiple tratados desde el año 1976 hasta el año 2006. Las variables estudiadas son: edad al diagnóstico y malignización, localización de la lesión, asociación familiar con otros tumores, hallazgos radiológicos, tratamientos aplicados, evolución en el … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) findings described in human medicine include extensive replacement of normal medullary cavity by cartilaginous tumors, showing T1‐weighted hypo‐ and T2‐weighted hyperintense signal associated with cartilaginous nature of the lesions, and decreased signal intensity representing mineralized cartilage matrix . When more than one lesion is detected, bone scintigraphy, demonstrating presence of multiple lesions with increased radiopharmaceutical uptake, has been recommended for screening of potential underlying enchondromatosis …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) findings described in human medicine include extensive replacement of normal medullary cavity by cartilaginous tumors, showing T1‐weighted hypo‐ and T2‐weighted hyperintense signal associated with cartilaginous nature of the lesions, and decreased signal intensity representing mineralized cartilage matrix . When more than one lesion is detected, bone scintigraphy, demonstrating presence of multiple lesions with increased radiopharmaceutical uptake, has been recommended for screening of potential underlying enchondromatosis …”
Section: Discussionsupporting
confidence: 81%
“…Specific therapy for enchondromatosis has not been described in veterinary medicine . In human medicine, curettage and graft filling for ostheosynthesis or corrective surgery for deformities, through osteotomy or stretching, are deemed surgical choices, unless these lesions being asymptomatic . Follow‐up recommendations for these lesions have been recently published in human literature, because risk of malignancy has been widely documented .…”
Section: Discussionmentioning
confidence: 99%
“…3 Chondroma is a benign cartilaginous tumor that escapes growth regulation and impairs normal bone development, often in a metaphyseal location. 4 Its gravity is related to potential malignant progression to chondrosarcoma. 5 Involvement often predominates on one side and can lead to varying degrees of deformity, limb length differences or pathological fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Vázquez-Garcia et al 4 more recently reported two similar cases treated by resection and who were both living at 17 years, although no details on reconstruction procedures were given. With regard to grade II chondrosarcomas, Schaison et a l. 13 reported 4 patients who underwent two disarticulations, one amputation and resection followed by reconstruction with a total knee prosthesis, but with no indication of the nature of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Ollier disease is a rare non-hereditary skeletal disorder characterized by the presence of multiple enchondromas (enchondromatosis), and these cartilaginous lesions can be limited to one limb, or localized to one half of the body [1, 2]. The disease often manifests in infancy and early childhood, usually starting with the appearance of palpable and painless bony masses on the involved limbs.…”
Section: Introductionmentioning
confidence: 99%